2017
DOI: 10.1002/ecs2.1719
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms underlying abundance and diversity responses of nematode communities to plant diversity

Abstract: Abstract. Plant diversity is known to influence the abundance and diversity of belowground biota; however, patterns are not well predictable and there is still much unknown about the driving mechanisms. We analyzed changes in soil nematode community composition as affected by long-term manipulations of plant species and functional group diversity in a field experiment with plant species diversity controlled by sowing a range of 1-60 species mixtures and controlling non-sown species by hand weeding. Nematode co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 59 publications
(162 reference statements)
6
31
1
Order By: Relevance
“…, Cortois et al. ). Indeed, previous work in grassland plant diversity experiments has shown that the functional composition of soil nematode communities is significantly affected by plant diversity (De Deyn et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Cortois et al. ). Indeed, previous work in grassland plant diversity experiments has shown that the functional composition of soil nematode communities is significantly affected by plant diversity (De Deyn et al.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of soil microorganisms in biodiversity-productivity relationships has been shown before (Maron et al 2011, Schnitzer et al 2011, Wagg et al 2011a, b, Latz et al 2012, we here focused on nematode communities. Nematodes represent the most abundant metazoans on Earth and are likely to exert various effects on plant growth, potentially providing a mechanistic explanation of PSFs (van der Putten et al 1993, Cortois et al 2017. Indeed, previous work in grassland plant diversity experiments has shown that the functional composition of soil nematode communities is significantly affected by plant diversity (De Deyn et al 2004, Viketoft et al 2009, Eisenhauer et al 2011, with likely feedback effects on plant growth and subsequently biodiversity-productivity relationships (Eisenhauer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our increased root productivity of L+T mixtures had neutral effects on nematode abundances. These results are in line with Cortois et al (2017) who show a decrease of plant-feeding nematode density…”
Section: Winter Cover Crop Legacy Effects On Soil Propertiessupporting
confidence: 92%
“…Increased plant productivity could lead to increased feeding area for herbivorous nematodes (Thoden, Korthals & Termorshuizen 2011). Also, increase of bottom-up resource quantity (Chen et al 2016) or quality (Cortois et al 2017) can stimulate nematode herbivory. Additionally, mixtures were expected to dilute the abundance of nematode host plants, resulting in neutral to negative mixture effects.…”
Section: Winter Cover Crop Legacy Effects On Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation